Kemandirian Belajar dan Kecerdasan Logika Terhadap Prestasi Belajar Fisika Pada Mahasiswa Jurusan Teknik Informatika Semester 1 STMIK Pranata Indonesia Bekasi - Maria Rosanti (Epsilon Journal of Management, 2025)
The purpose of this study is to determine the effect of learning independence and logical intelligence on Physics learning achievement in 1st semester students of STMIK Pranata Indonesia Bekasi Odd Semester 2021/2022 Department of Informatics Engineering with survey research methods. Student research respondents totaled 45 people, selected based on purpose sampling techniques. Data collection is carried out by distributing questionnaires directly to the sample. Data analysis uses descriptive statistics such as finding the mean, median, mode, standard deviation, and inferential statistics to find coefficients. The method in this study is a survey. That there is a change in the dependent variable, which is 40.8% and the remaining 59.2% which is influenced by variables other than variables X1 and X2. Because the value of F = 14.457 is used to test the hypothesis in predicting the contribution of independent variables (X1 and X2) to the dependent variable (Y)